Immunosuppressive and antibacterial activities of dihydromorin and norartocarpetin isolated from artocarpus heterophyllus heartwoods - Abdi Wira, Septama; Ibrahim, Jantan; Panichayupakaranant, Pharkphoom; Mohd F. F., Mohd Aluwi; Eldiza Puji, Rahmi (Wolters Kluwer Medknow Publications, 2020)
Objective: To evaluate the immunosuppressive effect on human phagocytes and antibacterial activity of dihydromorin and norartocarpetin isolated from Artocarpus heterophyllus heartwoods. Methods: Dihydromorin and norartocarpetin were isolated from Artocarpus heterophyllus heartwoods. A modified Boyden chamber was used to determine the chemotactic activity of human phagocyte. The respiratory burst was evaluated by chemiluminescence assay. Myeloperoxidase (MPO) activity was quantified using a colorimetric assay. The broth microdilution method was performed to assess their antibacterial activity. Results: Dihydromorin exhibited potent inhibitory effect on the chemotactic activity of polymorphonuclear neutrophils (PMNs) with an IC50 value of 5.03 μg/mL. Dihydromorin also inhibited reactive oxygen species production of whole blood cells, PMNs, and monocytes with IC50 values of 7.88, 7.59 and 7.24 μg/mL, respectively. Interestingly, dihydromorin also strongly inhibited the MPO activity of PMNs with an IC50 value of 5.24 μg/mL, which was lower than indomethacin (24.6 μg/mL). Molecular docking of dihydromorin and crystal structure of MPO showed that dihydromorin had close interaction with key amino acid residues such as Arg239 and Gln91. Antibacterial activity assay showed that only dihydromorin had a strong effect against Streptococcus pyogenes with MIC and MBC values of 15.62 and 31.25 μg/mL, respectively. Conclusions: The results suggest that dihydromorin could be developed as an anti-inflammatory and antibacterial agent.